The Helicobacter pylori CagA protein disrupts matrix adhesion of gastric epithelial cells by dephosphorylation of vinculin - Moese, Stefan; Selbach, Matthias; Brinkmann, Volker; Karlas, Alexander; Haimovich, Beatrice; Backert, Steffen; Meyer, Thomas F. (Cellular Microbiology, 2007)
Helicobacter pylori colonizes the human stomach, contributing to or causing several diseases. Translocation of the CagA bacterial protein into gastric epithelial cells has been linked to an increased risk of peptic ulcer disease and gastric carcinoma. Upon translocation, CagA is tyrosine phosphorylated by Src family kinases (SFKs), which themselves become inactivated via a negative feedback loop. Here, we show that tyrosine-phosphorylated CagA disrupts adhesion of AGS cells to the extracellular matrix. Owing to the inactivation of c-Src via CagA interaction, vinculin is dephosphorylated at tyrosine residues, 100 and 1065, by corresponding phosphatases. Vinculin dephosphorylation disturbs the interaction and recruitment of the actin-related protein 2/3 (Arp2/3) complex by p34Arc, resulting in a reduction of focal adhesion complexes. These defects can be mimicked by downregulating vinculin using RNA interference in non-infected cells. Tyrosine dephosphorylation of vinculin results in severe cellular deficiencies in cell-matrix adhesion, cell spreading and wound repair. We hypothesize that CagA-mediated inactivation of vinculin is a key step in the mechanism by which H. pylori induces damage to the gastric epithelium and represents an important step in disease development. © 2007 The Authors; Journal compilation © 2007 Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up